Properties Of Glass Fibre Epoxy Laminated Composites With Electrospray Of Different Carbon Nanotubes Concentrations - Roslan, Putri Nur Salsabila (2020)
Laminated composite materials are used extensively in aerospace and other applications due to their high specific modulus and high specific strength. However, interlaminar fracture or delamination damage is the challenge in laminated composites. Therefore, the aim of this study is to improve the interlaminar of the laminated composites. The electrospray method was used to disperse the carbon nanotubes on the glass fiber. A vacuum-assisted resin transfer molding (VARTM) method was used to produce laminated glass fiber/epoxy with multi-walled carbon nanotube (MWCNT). The mode I fracture toughness, flexural, and fiber volume fraction was used to test and analyzed the properties of the composites. It is found that the mode I fracture toughness for laminated glass fiber with 0.5 wt % has high fracture toughness compared to the other composites. The flexural strength and modulus of laminated glass fiber- 0.5 wt% improved up to 7.12 % in flexural strength and 2.34 % in flexural modulus in comparison to control samples. However, laminated composites decrease in both flexural and fracture toughness when incorporate 0.8 wt % of CNT about 54.98% and 4.66% respectively. It might due to the thicker coating on the woven which can create agglomeration between nanotubes and lead to stress concentration. This can decrease in mechanical properties of the composites. In support, the void content of the laminated glass fiber-0.8 wt % has high values which are near to 0.02% compared to both control and 0.5 wt % CNTs laminated composites which are 0.01 %. In summary, laminated glass fiber when incorporating 0.5 wt % of CNTs was found to exhibit higher flexural and fracture toughness.